Thalamic feedback shapes brain responses evoked by cortical stimulation in mice and humans - Simone Russo; Leslie D. Claar; Giulia Furregoni; Lydia C. Marks; Giri Krishnan; Flavia Maria Zauli; Gabriel Hassan; Michela Solbiati; Piergiorgio d’Orio; Ezequiel Mikulan; Simone Sarasso; Mario Rosanova; et al. (Nature Communications)
Abstract Cortical stimulation with single pulses is a common technique in clinical practice and research. However, we still do not understand the extent to which it engages subcortical circuits that may contribute to the associated evoked potentials (EPs). Here we show that cortical stimulation generates remarkably similar EPs in humans and mice, with a late component similarly modulated by the state of the targeted cortico-thalamic network. We then optogenetically dissect the underlying circuit in mice, demonstrating that the EPs late component is caused by a thalamic hyperpolarization and rebound. The magnitude of this late component correlates with bursting frequency and synchronicity of thalamic neurons, modulated by the subject’s behavioral state. A simulation of the thalamo-cortical circuit highlights that both intrinsic thalamic currents as well as cortical and thalamic GABAergic neurons contribute to this response profile. We conclude that single pulse cortical stimulation engages cortico-thalamo-cortical circuits largely preserved across different species and stimulation modalities.